2022
DOI: 10.2147/jbm.s349070
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Initial Parenteral Iron Therapy Dosing and Treatment Effectiveness: A Real-World Retrospective Analysis

Abstract: Purpose Replacement iron is the main treatment for iron deficiency, but the relationship between initial intravenous (IV) dose and need for additional treatment is unclear. This study explored patterns of IV iron dosing in US clinical practice. Methods Patient records were obtained for adults who received IV iron for anemia between 2015 and 2017. Patients were classified into four groups: those who received <1500 mg and ≥1500 mg IV iron and those received ≤1000 mg and >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…This hypothesis is supported by the results of two real-world analyses that showed that higher-dose iron formulations can be more effective in managing anemia. LaVallee et al found that use of high-dose IV iron formulations for the initial course of treatment resulted in fewer outpatient visits and fewer retreatments [ 13 ]. In a retrospective analysis of integrated electronic health records and claims data in the USA, 77% of patients had an iron deficit of > 750 mg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis is supported by the results of two real-world analyses that showed that higher-dose iron formulations can be more effective in managing anemia. LaVallee et al found that use of high-dose IV iron formulations for the initial course of treatment resulted in fewer outpatient visits and fewer retreatments [ 13 ]. In a retrospective analysis of integrated electronic health records and claims data in the USA, 77% of patients had an iron deficit of > 750 mg.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to addressing the underlying causes of IDA, intravenous (IV) iron therapy is often required for patients with IDA who have chronic diseases and those who are not responsive to or who cannot tolerate oral iron [ 4 , 5 , 8 , 10 ]. Current IV iron therapies available in the USA include high-dose IV iron formulations such as ferric carboxymaltose (FCM), ferumoxytol, and ferric derisomaltose, and low-dose IV iron (LDI) formulations such as iron sucrose, iron dextran, and sodium ferric gluconate complex in sucrose [ 13 ]. High-dose IV iron formulations allow patients to receive more iron with fewer infusions than LDI and have been shown to allow more patients to achieve normal serum Hgb levels than LDI [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…The repository represents more than 98% of US payers and is nationally representative of the US, including patients from all geographic regions. The database has been applied in multiple peer-reviewed real-world retrospective analyses [ 22 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, the iron prescription pattern and whether adequate iron dose is prescribed in the actual clinical practice in Japan has not been clarified, and a survey of the current practice is warranted. In the U.S., the pattern of IV iron dosing, including FCM, has already been surveyed, showing that a higher total cumulative dose of iron was associated with improved Hb levels and reduced needs for further iron therapy [11]. However, because the types and dosages of available iron preparations in Japan differ from the U.S., a survey using Japanese data is needed.…”
Section: Introductionmentioning
confidence: 99%